2014
DOI: 10.1016/j.aop.2014.07.008
|View full text |Cite
|
Sign up to set email alerts
|

A physically based connection between fractional calculus and fractal geometry

Abstract: We show a relation between fractional calculus and fractals, based only on physical and geometrical considerations. The link has been found in the physical origins of the power-laws, ruling the evolution of many natural phenomena, whose long memory and hereditary properties are mathematically modelled by differential operators of non integer order. Dealing with the relevant example of a viscous fluid seeping through a fractal shaped porous medium, we show that, once a physical phenomenon or process takes place… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Instead, these models assume that the behaviour is captured in the fractal structure of the tissue [16,17]. Recent research has shown the relationship between fractals and fractional calculus, based on physical and geometric considerations [21]. It was noted in [17] that muscle fibers, tendon, and nerve fibers exhibit patterns that support the dynamics of these multiscale structures expressed by fractional-order models.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, these models assume that the behaviour is captured in the fractal structure of the tissue [16,17]. Recent research has shown the relationship between fractals and fractional calculus, based on physical and geometric considerations [21]. It was noted in [17] that muscle fibers, tendon, and nerve fibers exhibit patterns that support the dynamics of these multiscale structures expressed by fractional-order models.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that differential equations with fractional derivatives (FDEs) describe experimental data of anomalous diffusion more accurately. Although fractional-order derivatives were first introduced as a novel mathematical concept with unclear physical meaning, nowadays, a clear connection between diffusion over fractal spaces (such as networks of capillaries) and fractional-order dynamics has been established [15][16][17][18]. In particular, in anomalous diffusion the standard assumption that the mean square displacement x 2 is proportional to time does not hold.…”
Section: Introductionmentioning
confidence: 99%
“…There is a lot of research in this direction, such as fractional Fokker-Planck equations, fractional diffusion equations, fractional master equations, stochastic fractional equations, and so on [25][26][27][28][29][30][31][32]. Fractal features and macroscopic anomalous exploits of systems are connected to the order of fractional derivatives [33][34][35][36][37][38][39][40]. In addition, memory effects in physical models are presented by using fractional derivatives because of their non-local character [41].…”
Section: Introductionmentioning
confidence: 99%